2013
DOI: 10.1371/journal.pone.0064673
|View full text |Cite
|
Sign up to set email alerts
|

Separate Populations of Neurons in Ventral Striatum Encode Value and Motivation

Abstract: Neurons in the ventral striatum (VS) fire to cues that predict differently valued rewards. It is unclear whether this activity represents the value associated with the expected reward or the level of motivation induced by reward anticipation. To distinguish between the two, we trained rats on a task in which we varied value independently from motivation by manipulating the size of the reward expected on correct trials and the threat of punishment expected upon errors. We found that separate populations of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 87 publications
8
38
0
Order By: Relevance
“…S1f). Neurons in the lesioned area are known to fire to reward-predictive cues (Bissonette et al, 2013; O'Doherty et al, 2003; O'Doherty et al, 2004; Oleson et al, 2012; Roesch et al, 2009) and send output to VTA (Bocklisch et al, 2013; Grace and Bunney, 1985; Groenewegen et al, 1990; Mogenson et al, 1980; Voorn et al, 2004; Watabe-Uchida et al, 2012; Xia et al, 2011), supporting the proposal that this part of VS may influence dopaminergic prediction error signaling as proposed in neural instantiations of temporal difference reinforcement learning (TDRL) models (Daw et al, 2006; Joel et al, 2002). …”
Section: Resultssupporting
confidence: 58%
“…S1f). Neurons in the lesioned area are known to fire to reward-predictive cues (Bissonette et al, 2013; O'Doherty et al, 2003; O'Doherty et al, 2004; Oleson et al, 2012; Roesch et al, 2009) and send output to VTA (Bocklisch et al, 2013; Grace and Bunney, 1985; Groenewegen et al, 1990; Mogenson et al, 1980; Voorn et al, 2004; Watabe-Uchida et al, 2012; Xia et al, 2011), supporting the proposal that this part of VS may influence dopaminergic prediction error signaling as proposed in neural instantiations of temporal difference reinforcement learning (TDRL) models (Daw et al, 2006; Joel et al, 2002). …”
Section: Resultssupporting
confidence: 58%
“…These data suggest that activity in NAc represents the motivational value associated with chosen actions and might be critical for translating cue-evoked value signals into motivated behavior (Catanese and van der Meer, 2013; McGinty et al, 2013). Consitent with this hypothesis, we and others have shown that firing in NAc is significantly correlated with reaction time (Roesch et al, 2009; Bissonette et al, 2013; McGinty et al, 2013). …”
Section: Nucleus Accumbens Core Versus Dorsal Lateral Striatumsupporting
confidence: 66%
“…In these experiments, animals learn that conditioned stimuli (CS) predict potential rewards or the possibility of punishment. Typically, there are three trial types where the CS predicts: (1) a large reward (e.g., sucrose, juice); (2) a neutral condition or a small (or no) reward; and (3) a small (or no) reward with the threat of an aversive outcome, such as delivery of a bitter quinine solution, electric shock, or air puff to the eye (Rolls et al 1989; Roesch and Olson 2004; Roesch et al 2010a; Bissonette et al 2013; Matsumoto and Hikosaka 2009; Brischoux et al 2009; Anstrom et al 2009; Lammel et al 2011). If neurons encode value , neural activity should show a monotonic relationship during appetitive, neutral, and aversive trials (Fig.…”
Section: Value Versus Motivation and Saliencementioning
confidence: 99%